2006
DOI: 10.1542/peds.2005-2947
|View full text |Cite
|
Sign up to set email alerts
|

Relative Benefits of Stimulant Therapy With OROS Methylphenidate Versus Mixed Amphetamine Salts Extended Release in Improving the Driving Performance of Adolescent Drivers With Attention-Deficit/Hyperactivity Disorder

Abstract: This study validates the use of stimulants to improve driving performance in adolescents with attention-deficit/hyperactivity disorder. In the study, OROS methylphenidate promoted significantly improved driving performance compared with placebo and mixed amphetamine salts extended release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 23 publications
2
53
0
1
Order By: Relevance
“…Research has generally found evidence of improved driving among adolescent and adult drivers with ADHD medication use (Cox et al 2000(Cox et al , 2006Hechtman et al 1984;Sobanski et al 2008;Wolraich et al 2005). One follow-up study of adults who had been diagnosed with ADHD as children found that those who had received medication in childhood for their ADHD reported fewer collisions as adults compared to those who went untreated or to non-ADHD controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has generally found evidence of improved driving among adolescent and adult drivers with ADHD medication use (Cox et al 2000(Cox et al , 2006Hechtman et al 1984;Sobanski et al 2008;Wolraich et al 2005). One follow-up study of adults who had been diagnosed with ADHD as children found that those who had received medication in childhood for their ADHD reported fewer collisions as adults compared to those who went untreated or to non-ADHD controls.…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental, laboratory simulator studies have found better simulator driving performance in persons using ADHD medications compared to placebo control groups (Cox et al 2000(Cox et al , 2004(Cox et al , 2006. However, other research has shown poor concordance between laboratoryor clinic-based measures of response to ADHD medication and actual performance (Thompson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 6 studies of children, adolescents and adults treated with stimulants for a minimum of 4 years (2 with follow-up in adolescence and 4 in young adulthood) and with information on childhood treatment with stimulants, a substantial reduction in subsequent alcohol and other substance use disorders was found. 35 Similarly, a recent 10-year prospective follow-up study of 140 children with ADHD treated with stimulants found no significant increase or decrease in alcohol, drug or nicotine use disorders. 64 In patients diagnosed with comorbid substance use disorders, the results are also promising.…”
Section: Dovepressmentioning
confidence: 96%
“…They have also been shown to improve associated symptoms of adult ADHD, including self-esteem, social and family functioning, driving skills and substance use risk. [32][33][34][35] The most commonly used stimulants in the treatment of adult ADHD include methylphenidate hydrochloride preparations (MPH), dextroamphetamines (DEX) and mixed amphetamine salts levo amphetamine and dextroampheatmine (AMP). Pemoline, a weak stimulant medication, has been withdrawn from the market because of hepatotoxicity.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation